Competitive Sports Anxiety, Healing Imagery and Achievement Goal; Mediating Role of Coaching Feedback in Young Pakistani Athletes - Yumna Ali; Syeda Farhana Kazmi (Lithuanian Sports University, 2024)
Background. Sports psychology is integral to be taught both in academic settings and on practical athletic fields. This study considers students who are part of the physical education and sports department, whose responsibilities are twofold. Practical implications of managing sports anxiety, recovering from the ordeal of rehabilitation injuries, and achieving sports goals are crucial aspects of coaching feedback. Aim: to explore competitive sports anxiety among enrolled student-athletes, the role of healing imagery in athletic injury recovery, and the achievement goals in the sports of cricket, hockey, and squash, with the mediation of coaching feedback. Methods: Purposive sampling was utilized to investigate 58 athletes on the psychological constructs of Competitive Sports Anxiety (Cox et al., 2003), Healing Imagery in Athletic Injury Scale (Cressman, 2010), Achievement Goal in Sports (Sean et al., 2008), and Coaching Feedback (Stein, 2009) across three prevalent sports: cricket, hockey, and squash in the region. Results Moderate, significant correlations are observed among the variables. There is a highly significant and positive impact of healing imagery on athletes' achievement goals, both in terms of ego and mastery. Coaching characterized by positivity and punishment orientation significantly affects goal achievement. Healing imagery serves as a partial mediator between competitive sports anxiety and athletes' achievement goals. Conclusion. Competitive sports anxiety can hinder the effectiveness of healing imagery and steer athletes away from achieving their goals. When athletes have mastered their sport, they are less inclined to utilize healing visualization techniques. As a result, coaches must adapt their teaching strategies to cater to the individual needs of athletes. Providing sports students and active players with regular sports psychological workshops and access to the latest therapies is essential. Exploring the motivational climate is integral for future studies. Keywords: competition, sports anxiety, healing imagery, achievement goal, coaching feedback